A late Cisuralian (early Permian) brachiopod fauna from the Taungnyo Group in the Zwekabin Range, eastern Myanmar and its biostratigraphic, paleobiogeographic, and tectonic implications. (November 2021) - Xu, Hai-peng; Aung, Kyi Pyar; Zhang, Yi-chun; Shi, G.R.; Cai, Fu-long; Zaw, Than; Ding, Lin; Sein, Kyaing; Shen, Shu-zhong
Abstract: The tectonic evolution of the Sibumasu Block during the Permian remains controversial, and Permian faunas and their paleobiogeographic affinities provide some insight into its paleogeographic and tectonic evolutionary histories. In this paper, a new brachiopod fauna dominated by Spinomartinia prolifica Waterhouse, 1981 is described from the uppermost part of the Taungnyo Group in the Zwekabin Range, eastern Myanmar. This brachiopod fauna includes 23 species and its age is well constrained as late Kungurian by the associated conodonts, i.e., Vjalovognathus nicolli Yuan et al., 2016 and Mesogondolella idahoensis (Youngquist, Hawley, and Miller, 1951 ), contrary to the late Sakmarian age given to the same brachiopod faunas previously reported from southern Thailand and Malaysia. Based on comprehensive comparisons of the Cisuralian brachiopod faunas and other data in different parts of the Sibumasu Block, we consider that they are better subdivided into two independent stratigraphic assemblages, i.e., the lower (earlier) Bandoproductus monticulus-Spirelytha petaliformis Assemblage of a Sakmarian to probably early Artinskian age, and the upper (younger) Spinomartinia prolifica-Retimarginifera alata Assemblage of a late Kungurian age. The former assemblage is a typical cold-water fauna, mainly composed of Gondwanan-type genera, e.g., Bandoproductus Jin and Sun, 1981, Spirelytha Fredericks, 1924, and Sulciplica Waterhouse, 1968 . The latter assemblage is strongly characterized by an admixture of both Cathaysian and Gondwanan elements, as well as some genera restricted to the Cimmerian continents. Notably, the spatial distribution pattern of these two separate brachiopod assemblages varies distinctly. The Sakmarian cold-water brachiopod faunas have been found in association with glacial-marine diamictites throughout the Sibumasu Block including both the Irrawaddy and Sibuma blocks. In contrast, the Kungurian biogeographically mixed brachiopod faunas are only recorded in the Irrawaddy Block, unlike the Sibuma Block that contains a contemporaneous paleotropical Tethyan fusuline fauna. Thus, it appears likely that by the end of Cisuralian (early Permian), the Sibumasu Block comprised the Irrawaddy Block in the south with cool climatic conditions, and the Sibuma Block in the north with a temperate to warm-water environment, separated by the incipient Thai-Myanmar Mesotethys.